On the theory and methodology of role : a contribution towards an interactive paradigm : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Bates, Richard Jeremy (Massey University, 1976)
This thesis (i) presents a critique of structural and socialisation perspectives in role theory, (ii) argues for a philosophical and theoretical position of transindividualism in the explanation of behaviour, (iii) examines the compatibility of current psychological and sociological theories with such a position, (iv) reviews discontinuities between theory methodology and interpretation in studies of role, (v) develops a comprehensive theoretical model for the analysis of individual and social system interactions via the mediating concept of role, (vi) presents a methodology appropriate to the examination of the general model in respect to a small scale social system, (vii) reports the results of the empirical investigation, and (viii) summarises and discusses the relevance of these findings to the proposed theoretical and methodological issues. It is concluded that both theory and methodology, having been supported by the empirical investigation of a small scale social system, might usefully be further applied to larger and more complex social systems.
Keywords: Role theory; Behaviour; Social interaction